2021
DOI: 10.1177/0011392120964892
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border reproductive care: Opinions and attitudes of society towards surrogate pregnancy

Abstract: Surrogate pregnancy (SP) has acquired a prominent public profile through the bioethical, legal and media debates this cross-border reproductive practice has raised worldwide. The different social agents involved in the phenomenon frequently appeal to public opinion looking for legitimation and endorsement of their ethical and political positions on the matter. However, opinion polls occupy a marginal place in research about SP. The article presents the findings of the scoping review of 31 scientific articles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It is a surprising result, since 65% of participants in this study did not have children. Other findings in a review conducted by Rodriguez-Jaume et al, (2021) suggest that social acceptance of surrogacy and positive attitude was not higher among people with infertility [ 13 ]. Six of the eight studies including infertile groups showed acceptance rates below the average overall value [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is a surprising result, since 65% of participants in this study did not have children. Other findings in a review conducted by Rodriguez-Jaume et al, (2021) suggest that social acceptance of surrogacy and positive attitude was not higher among people with infertility [ 13 ]. Six of the eight studies including infertile groups showed acceptance rates below the average overall value [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…What is interesting, social acceptance of surrogacy was not higher among people with infertility. Six of the eight studies, including infertile groups, showed acceptance rates below the average overall value [ 13 ]. Research among the Spanish population has shown that 60.1% of respondents claimed that surrogacy is a “good way to help infertile or homosexual couples to have a child”[ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that the repurchase rate is an important indicator affecting the platforms, created an impact model for the repurchase rate through the simulation method, and predicted the actual repurchase effect. However, the conventional analysis method for the factors affecting the repurchase rate mainly uses SPSS17.0 to obtain the in uencing factors, which is vulnerable to the impact of customer experience competition [17][18][19] , leading to high variance between the analysis groups of in uencing factors,It does not meet the current analysis needs. Therefore, this paper designs a new analysis method of factors affecting the repurchase rate of Hainan cross-border ecommerce platform based on user experience.…”
Section: Introductionmentioning
confidence: 99%